2020
DOI: 10.3389/fneur.2020.00572
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Regional Cerebral Blood Flow in Children With Newly-Diagnosed Type 1 Diabetes Mellitus: An Arterial Spin Labeling Perfusion Magnetic Resonance Imaging Study

Abstract: Object: Diabetes is associated with cerebral vascular dysfunction and increased vascular cognitive impairment. The objective of this study was to use arterial spin labeling (ASL) perfusion-weighted magnetic resonance imaging to investigate whether cerebral perfusion was changed in newly-diagnosed children with type 1 diabetes mellitus (T1DM) and the possible relationship between aberrant cerebral blood flow (CBF) with cognitive as well as clinical variables. Methods: Between January 2017 and February 2018, 34 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
2
0
2
Order By: Relevance
“…Precentral gyrus is a part of the premotor area and the supplementary motor area, which integrate the incoming sensory information from the outside world and the current state of bod ( Hooks, 2017 ). Existing studies have suggested that changes in the neurovascular coupling and cerebral perfusion patterns in the motor region are related to motor development ( Song et al, 2020 ). We also observed decreased negative CBF connectivity between the right caudate and the right lingual gyrus as well as the right preceneus.…”
Section: Discussionmentioning
confidence: 99%
“…Precentral gyrus is a part of the premotor area and the supplementary motor area, which integrate the incoming sensory information from the outside world and the current state of bod ( Hooks, 2017 ). Existing studies have suggested that changes in the neurovascular coupling and cerebral perfusion patterns in the motor region are related to motor development ( Song et al, 2020 ). We also observed decreased negative CBF connectivity between the right caudate and the right lingual gyrus as well as the right preceneus.…”
Section: Discussionmentioning
confidence: 99%
“…Патофизиологические механизмы, лежащие в основе когнитивных нарушений, связанных c СД 1 типа, сложны и многофакторны: как гипогликемия, так и гипергликемия могут способствовать когнитивным нарушениям при данной патологии [6]. Многие исследования брали за основу роль гипогликемии в данном процессе, однако крупное продольное эпидемиологическое исследование не выявило такой связи [7].…”
Section: Discussionunclassified
“…В данном иссле довании наибольшее значение, кроме гипергликемии, имели анамнестические данные, длительность заболевания, уровень холестерина и степень АГ, которые являются общими для развития нейродегенеративного процесса [17]. Дисгликемия была подтверждена не во всех работах, так, при манифестации уровень HbA 1c не показал ассоциацию с гипоперфузией головного мозга, тогда как хроническая гипергликемии при СД 2 типа была связана с более низким общим церебральным кровотоком в височной области [6,18].…”
Section: Discussionunclassified
“…A study examining children aged 6-11 with T1DM found that structural changes in the brains of children with T1DM were associated with CI and that they tend to have poor glycemic control compared with controls [10]. In newly diagnosed children with T1DM, the researchers found reduced cerebral blood perfusion in the visual and sensorimotor areas of the cerebral cortex [15]. Moreover, compared with non-diabetic children, T1DM children exhibited significantly lower performance on the full IQ and motor speed tests.…”
Section: Children and Adolescentsmentioning
confidence: 99%